The Jurisdiction of the Corruption Eradication Commission and Military Police in Addressing Corruption in Military Procurement - Zainudin Syah Pahlavi; Erny Herlin Setyorini (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
The aim of this research is to ascertain how the corruption eradication commission and the military police are involved in handling corruption crimes in the military environment. The method used in this study is normative juridical by using a statutory approach and a conceptual approach. Corruption in the procurement of goods and services in the military has its own challenges because it involves strategic materials and defense projects. The Military Police plays an important role in investigating military personnel involved in corruption, especially in maintaining military discipline. The Corruption Eradication Commission has broad authority to investigate corruption cases, including those involving military personnel. However, for the prosecution process, cases involving military personnel must be heard in Military Courts. The results of this study show that the balance between the military civil justice system is essential for effective law enforcement in corruption cases in the military environment.